Explosive music, bodies & minds: the experience of the EXPLOSION image-schema in electronic dance music - Marchiano, María (2023)
Aims: Identify the experiential concepts that result from the instantiation of the EXPLOSION image-schema as reported by participants of electronic dance music parties. Analyse the correspondence between the EXPLOSION image-scheme domain and the abstract concepts to which it refers.